LOFAR-Boötes: properties of high- and low-excitation radio galaxies at 0.5 < z < 2.0. Issue 3 (17th January 2018) - Williams, W L; Calistro Rivera, G; Best, P N; Hardcastle, M J; Röttgering, H J A; Duncan, K J; de Gasperin, F; Jarvis, M J; Miley, G K; Mahony, E K; Morabito, L K; Nisbet, D M; et al.
Abstract: This paper presents a study of the redshift evolution of radio-loud active galactic nuclei (AGN) as a function of the properties of their galaxy hosts in the Boötes field. To achieve this we match low-frequency radio sources from deep 150-MHz LOFAR (LOw Frequency ARray) observations to an I -band-selected catalogue of galaxies, for which we have derived photometric redshifts, stellar masses, and rest-frame colours. We present spectral energy distribution (SED) fitting to determine the mid-infrared AGN contribution for the radio sources and use this information to classify them as high- versus low-excitation radio galaxies (HERGs and LERGs) or star-forming galaxies. Based on these classifications, we construct luminosity functions for the separate redshift ranges going out to z = 2. From the matched radio-optical catalogues, we select a sub-sample of 624 high power ( P 150 MHz > 10 25 W Hz −1 ) radio sources between 0.5 ≤ z < 2. For this sample, we study the fraction of galaxies hosting HERGs and LERGs as a function of stellar mass and host galaxy colour. The fraction of HERGs increases with redshift, as does the fraction of sources in galaxies with lower stellar masses. We find that the fraction of galaxies that host LERGs is a strong function of stellar mass as it is in the local Universe. This, combined with the strong negative evolution of the LERG luminosity functions over this redshift range, is consistent with LERGs being fuelled by hot gas in quiescent galaxies.